Comparative analysis of polymorphisms of the serotonin receptor genes HTR1A, HTR2A, and HTR1B in Hadza and Datoga males - Sukhodolskaya, E. M; Vasilyev, V. A; Shibalev, D. V; Shcherbakova, O. I; Kulikov, A. M; Lazebny, O. E; Karelin, D. V; Butovskaya, M. L; Ryskov, A. P (Russian journal of genetics, 2015)
The distribution of the allele and genotype frequencies of polymorphic loci of serotonin receptor genes (HTR1A, rs6295; HTR2A, rs6311; HTR1B, rs6296) in Hadza (n = 197) and Datoga males (n = 230) living in Tanzania was determined. It was shown that the populations significantly differ by the frequencies of alleles and genotypes of the rs6295 locus of the HTR1A gene. The G-allele (0.779) and the genotype G/G (0.590), which are markers of increased risk of suicidal and impulsive behavior, respectively, are revealed in Hadza with high frequency. It was found that the frequency of homozygous G/G of the rs6296 locus of the HTR1B gene, which is a marker of increased risk of outward directed aggression, is higher in Datoga (0.563) than in Hadza (0.457). The allele and genotype frequencies of the rs6311 locus of the HTR2A gene do not differ among the Hadza and Datoga males. The data on the distribution of allele and genotype frequencies of the HTR1A, HTR2A, and HTR1B genes can be used to determine the associations of the identified markers with various forms of human aggressive behavior.